Inspector Lewis. Series 5 [videorecording (DVD)] - Whately, Kevin; Fox, Laurence; Holman, Clare; Dexter, Colin (Distributed by PBS Distribution, 2012)
With his young partner DS Hathaway, they continue solving cases in the seemingly perfect academic haven of Oxford.